The Students’ Acceptance on Provided and Students’ Own Dialogue on The Students’ Speaking Improvement - Juliansyah; Bambang Trisno Adi; Harun, Yessy (JEE (Journal of English Education), 2022)
This study is about how 55 university students perceive the learning system on communication skill through virtual class by using provided dialogue and students’ own dialogue. Provided dialogue means text of conversation taken from the book, and the lecturer brings it in the virtual class for the students to discuss, learn, and practice. Meanwhile, the students’ own dialogue refers to the assignment the lecturer gives to students in which students create dialogue within 5-6 days and the dialogue must fulfil several requirements. The instrument for collecting data is questionnaire. There are 21 items of questions in questionnaire given to students at the end of semester. The study proves that the usage of provided dialogue and plus the students’ own dialogue makes the zoom class more interesting. Other findings are the students are able to use specific expressions in communication using dialogue, in good intonation and pronunciation, in good spelling and grammar, and appropriate gestures and full confidence. Furthermore, the questionnaire also shows good point on the students’ improvements after the students have learned communication skill using both provided dialogue and the students’ own dialogue.